ChemInform Abstract: A Novel Approach for Highly Regio‐ and Stereoselective Synthesis of (Z)‐3‐Methyleneisoindoline‐1‐ones in Aqueous Micellar Medium. Issue 14 (20th March 2013) - Sarkar, Swarbhanu; Dutta, Samrat; Dey, Rajdip; Naskar, Subhendu
Abstract The optimized conditions allow an efficient and rapid approach to the biologically important heterocyclic ring system.